Effect of Family Structure and Behavioral and Eyesight Problems on Caries Severity in Pupils by Using an Ordinal Logistic Model - Kazem Mohammad; Keramat Nourijelyani; Abbas Rahimi Foroushani; Mohammad Reza Eshraghian; Yunes Jahani; Arash Shahravan; Mahin Alam (Tehran University of Medical Sciences, 2013)
Background: Dental caries is one of the most preventable yet prevalent chronic diseases worldwide. Our objective was to evaluate the effect of family structure and behavioral and eyesight problems as they relate to caries severity in schoolchildren.Methods: This research was carried out on 845 primary schoolchildren aged 9 yr in Kerman, Iran, in 2012. Ten variables, including health records, family structure information and a dmft/DMFT index, were collected. Children were categorized into three groups based on the WHO caries severity classification. Low caries level was defined as dmft/DMFT<2.6, moderate as dmft/DMFT of 2.7-4.4 and high as dmft/DMFT>4.4. The Cochran-Armitage test and ordinal logistic regression were employed for data analysis.Results: Almost half of pupils had moderate or high caries severity. The odds of being in a higher caries severity category in pupils with behavioral problems (OR=2.37, 95% CI: 1.29-4.38) and girls (OR=1.6, 95% CI: 1.22-2.06) were higher than in other categories. In addition, pupils with eyesight problems (OR=0.58, 95% CI: 0.37-0.90) and overweight pupils (OR=0.46, 95% CI: 0.31-0.71) had lower caries severity than others. The effects of parents' education, birth rank, living with parents and consanguineous relationship between parents were not significant on caries severity (P>0.05).Conclusions: Female pupils with behavioral problems were at a higher risk of caries severity than other pupils. These pupils need to be educated and coached on proper dental care. In addition, overweight pupils and those with eyesight problems had less caries severity than others. Family structure in this study did not have an effect on the severity of dental caries.